Microstructure and electrochemical properties of plasma tantalumising on low carbon steel. (August 2015) - Wang, Y.; Zhang, P.-Z.; Wu, H.-Y.; Wei, X.-F.; Bi, Q.; Song, J.
Abstract : Tantalum coating was successfully prepared onto Q235 low carbon steel substrate by a double glow plasma technique to improve the corrosion resistance. The microstructure and chemical composition of the coating were investigated by SEM, energy dispersive spectrometry and X-ray diffraction. The tantalum coating consisted of deposition layer, and the diffusion layer is ∼33 μm in thickness, metallurgically adhered to the substrate. Nanoindentation tests were used to measure nanomechanical properties of the coating and the substrate. A comparative study of the corrosion resistance of the bared and tantalum coated steel was conducted by electrochemical measurements in 3·5 wt-%HCl solution respectively. The results show that the coated samples exhibit much higher hardness and better anticorrosion performance than the uncoated ones. The excellent corrosion resistance of tantalum coated steel was attributed to the low porosity for the coating and a compact, and the stable tantalum oxidation film formed on the surface of the steel to prevent the substrate contact with hydrochloric acid electrolyte.